Inheritance of resistance to angular leaf spot in common bean and validation of the utility of resistance linked markers for marker assisted selection out side the mapping population - Namayanja, AR; Buruchara, Robin Arani; Mahuku, George S.; Rubaihayo, P.R.; Kimani, P.M.; Mayanja, S.; Eyedu, H (Springer, 2006)
Inheritance of resistance to angular leaf spot (ALS) disease caused by Phaeoisariopsis griseola (Sacc.) Ferr was investigated in two common bean cultivars, Mexico 54 and BAT 332. Both Andean and Mesoamerican backgrounds were used to determine the stability of the resistance gene in each of the two cultivars. Resistance to P. griseola was phenotypically evaluated by artificial inoculation with one of the most widely distributed pathotypes, 63–39. Evaluation of the parental genotypes, F1, F2 and backcross populations revealed that the resistance to angular leaf spot in the cultivars Mexico 54 and BAT 332 to pathotype 63–39 is controlled by a single dominant gene, when both the Andean and Mesoamerican backgrounds were used. Allelism test showed that ALS resistance in Mexico 54 and BAT 332 to pathotype 63–39 was conditioned by the same resistance locus. Resistant and susceptible segregating populations generated using Mexico 54 resistant parent were selected for DNA extraction and amplification to check for the presence /absence of the SCAR OPN02 and RAPD OPE04 markers linked to the Phg-2 resistance gene. The results indicated that the SCAR OPN02 was not polymorphic in the study populations and therefore of limited application in selecting resistant genotypes in such populations. On the other hand, the RAPD OPE04 marker was observed in all resistant individuals and was absent in those scored susceptible based on virulence data. Use of the RAPD OPE04 marker in marker-assisted selection is underway.